2016
DOI: 10.1002/art.39670
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Herpes Zoster in Autoimmune and Inflammatory Diseases: Implications for Vaccination

Abstract: Objective. The herpes zoster (HZ) vaccine is recommended for adults in the US ages ‡60 years who do not have weakened immune systems. It is unclear how the risk of HZ varies according to age and disease conditions in younger patients with autoimmune or inflammatory (AI) diseases. This study was undertaken to evaluate the age-stratified incidence of HZ in patients with AI diseases as compared to older adults for whom the HZ vaccine is currently recommended by the US Centers for Disease Control and Prevention.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
138
2
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 36 publications
14
138
2
13
Order By: Relevance
“…In unvaccinated healthy older people in the SPS, the absolute IR was 1.1 per 100py in patients age 70 and older. Rates in our study were approximately 50% increased, consistent with prior observations that have found elevated rates of HZ in autoimmune disease patients (18). …”
Section: Discussionsupporting
confidence: 93%
“…In unvaccinated healthy older people in the SPS, the absolute IR was 1.1 per 100py in patients age 70 and older. Rates in our study were approximately 50% increased, consistent with prior observations that have found elevated rates of HZ in autoimmune disease patients (18). …”
Section: Discussionsupporting
confidence: 93%
“…This is important because patients with RA already have an elevated HZ risk compared with the general population 4 5. HZ complications can cause significant morbidity, for example chronic, debilitating pain syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…95 Additional literature is emerging suggesting that younger adults with autoimmune diseases or inflammatory conditions have rates of herpes zoster that are comparable to or greater than the rates in older adults and that this population should be considered for vaccination at a younger age cut off. 96 How this would impact our vaccination practices as patients with rheumatologic diseases age is unknown. Further research is needed in older adults with rheumatologic diseases and multimorbidity to determining vaccine efficacy and scheduling.…”
Section: Gaps/challenges In Current Geriatric Rheumatology Clinical Carementioning
confidence: 99%